Liver cirrhosis in the Hospital General de Arequipa, Peru - Fernán Zegarra P., L. A. (1967)
Knowledge of the Geographical Pathology in Spain and Latin America, is of great importance for their projections on the adequacy of resources and better plans for the treatment of disease. The study of them is in a better position than before, to have new technical methods to try to solve problems etiologic and pathogenetic position. The Liver Cirrhosis, as a research topic is always topical and worth, in a baseline survey, make a concerted effort sacrificing individual views to homogenize results. It is for this reason that our work is, in general, the criterion Gall (8) in the classification of Liver Cirrhosis.